Use a rotation of axes to eliminate the cross product term in the equation.
7y^2 + 24xy-9 = 0
solve for y
D= (24x)^2 -4*7(-9) = 576x^2+252
y = --24x+(576x^2+252)^1/2/ 2*24x
y1 = -12x+(144x^2 +63)^1/2/24x
y2 = -12x-(144x^2 +63)^1/2/24x
Regarding any clarification plz let me know .
I will explain you feel any doubt.
I hope it will be clear now
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?